A Skills beyond School Review of Austria - Musset, Pauline (OECD Reviews of Vocational Education and Training, 2013)
This report examines vocational education and training programmes in Austria, covering how they are changing, how they are funded, how they are linked to academic and university programmes and how employers and unions are engaged